A virtual high-throughput screening approach to the discovery of novel inhibitors of the bacterial leucine transporter, LeuT. (March 2013) - Simmons, Katie J.; Gotfryd, Kamil; Billesbølle, Christian B.; Loland, Claus J.; Gether, Ulrik; Fishwick, Colin W. G.; Johnson, A. Peter
Abstract Membrane proteins are intrinsically involved in both human and pathogen physiology, and are the target of 60% of all marketed drugs. During the past decade, advances in the studies of membrane proteins using X-ray crystallography, electron microscopy and NMR-based techniques led to the elucidation of over 250 unique membrane protein crystal structures. The aim of the European Drug Initiative for Channels and Transporter (EDICT) project is to use the structures of clinically significant membrane proteins for the development of lead molecules. One of the approaches used to achieve this is a virtual high-throughput screening (vHTS) technique initially developed for soluble proteins. This paper describes application of this technique to the discovery of inhibitors of the leucine transporter (LeuT), a member of the neurotransmitter:sodium symporter (NSS) family.